2020
DOI: 10.1111/oik.06898
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effects in zooplankton consumers are not only mediated by direct but also by indirect effects of phosphorus limitation

Abstract: Nutrient limitation of primary producers has repeatedly been shown to negatively affect consumers, directly through stoichiometric mismatch and indirectly via alterations in the producer's biochemical quality or palatability. In this study, we assessed whether direct and indirect impacts of phosphorus‐limitation on a planktonic consumer are transferred to the next generation via maternal effects and whether these effects reflect an anticipatory adaptive strategy. For this, we subjected cultures of the algivoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
(79 reference statements)
2
9
0
Order By: Relevance
“…Irrespective of the molar C:P ratio of the food, rotifer populations fed P-supplemented algae with a growth history under P-limiting conditions (i.e., MP LP?P and HP LP?P ) systematically underperformed compared to rotifers that had been fed algae grown under intermediate or high P levels (MP chem and HP chem ). This observation is consistent with other studies (Rothhaupt 1995;Zhou et al 2018;Zhou and Declerck 2020) that observed and explained such growth rate reductions by indirect non-stoichiometric changes in algal traits associated with P-limited growth, e.g., biochemical composition (Spijkerman and Wacker 2011;Challagulla et al 2015) or morphology (van Donk and Hessen 1995;van Donk et al 1997). Alternatively, such effect of growth history could be interpreted as the result of adverse effects of the P-supplementation treatment, but then one would expect that the magnitude of such effect should increase with increasing amounts of supplemented P. However, we found no empirical support for this expectation given the absence of a statistical interaction between food P content and growth history.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Irrespective of the molar C:P ratio of the food, rotifer populations fed P-supplemented algae with a growth history under P-limiting conditions (i.e., MP LP?P and HP LP?P ) systematically underperformed compared to rotifers that had been fed algae grown under intermediate or high P levels (MP chem and HP chem ). This observation is consistent with other studies (Rothhaupt 1995;Zhou et al 2018;Zhou and Declerck 2020) that observed and explained such growth rate reductions by indirect non-stoichiometric changes in algal traits associated with P-limited growth, e.g., biochemical composition (Spijkerman and Wacker 2011;Challagulla et al 2015) or morphology (van Donk and Hessen 1995;van Donk et al 1997). Alternatively, such effect of growth history could be interpreted as the result of adverse effects of the P-supplementation treatment, but then one would expect that the magnitude of such effect should increase with increasing amounts of supplemented P. However, we found no empirical support for this expectation given the absence of a statistical interaction between food P content and growth history.…”
Section: Discussionsupporting
confidence: 94%
“…P-supplementation to algae has been applied for two major aims. In one type of studies, the method has been used to compare the relative impact of direct with indirect, non-stoichiometric impacts of P-limitation (Rothhaupt 1995;Zhou et al 2018;Zhou and Declerck 2020). Typically, two types of algal cultures are set up under P-sufficient (HP) and P-limited (LP food) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We counted the remaining animals to estimate PGR and preserved them in 4% formalin 132 solution. Data from the first five days were omitted from the calculations to avoid maternal effects from 133 previous culturing conditions (Zhou & Declerck 2020). To determine the fraction of sexual females for 134 each replicate, we examined all preserved individuals and determined the number and type of eggs they 135 carried (Appendix S1).…”
Section: Common Garden One (Cg1): Pgr and Fraction Of Sexual Individumentioning
confidence: 99%
“…A theory of ecological stoichiometry suggests that the carbon content of primary producers relative to their nutrient content such as nitrogen or phosphorus is an important property affecting growth efficiency in herbivores 4 . Supporting the theory, a number of studies have shown that growth rate in terms of carbon accumulation relative to ingestion rate strongly depends on the carbon contents of the food relative to nutrients [26][27][28][29] . Thus, k can be expressed as:…”
Section: Resultsmentioning
confidence: 91%
“…As our traps often contained no fish, we used θ ¼ CPUE þ 1. For α nut , we focused on phosphorus since freshwater limnetic ecosystems are primarily phosphorus limited 17,18 and as growth of zooplankton is affected by relative phosphorus in algae [26][27][28][29] . Specifically, we used the carbon to phosphorus ratio of seston as a surrogate for α nut because this ratio has been generally used in consideration of ecological stoichiometry in freshwater 4 .…”
Section: Methodsmentioning
confidence: 99%